INTEGRATIVE PARADIGM OF ISLAMIC LEGAL POLITICS: RECONCEPTUALIZATION OF TRANSFORMATION AND HARMONIZATION WITHIN THE PLURALISTIC NATIONAL LEGAL SYSTEM - Taroman Pasyah; Dedeng; Taslim; Rd. Muhammad Ikhsan; Akhmad Idris; Yanuar Syam Putra (Fakultas Hukum Universitas Sriwijaya, 2026)
Abstract: This study aims to analyze the dynamics of the political development of Islamic law in the Indonesian national legal system, the relationship between Islamic law, the state, and legal pluralism, as well as the transformation and harmonization strategy of Islamic law based on literature review. The research uses a qualitative method with a non-systematic literature review approach to sixteen journal articles relevant to the political theme of Islamic law in Indonesia. Data collection techniques are carried out through identification, classification, and analysis of previous research documents, while data analysis uses content analysis and descriptive-qualitative analysis. The results of the study show that Islamic legal politics in Indonesia develops historically, gradually, and dynamically through the process of legislation, harmonization, and political negotiation within the framework of a pluralistic Pancasila legal state. Islamic law developed not only in the field of family law and religious justice, but also in the sharia economic sector, waqf, zakat, and sharia-based social security. The study also found that the relationship between Islamic law, the state, and legal pluralism is dialogical and compromiseal, while the transformation of Islamic law is carried out through a substantive, inclusive, and contextual approach. This study concludes that Islamic legal politics in Indonesia develops through the strategy of integrating sharia values with the principles of democracy, legal pluralism, and modern national legal development.